THE IMPACT OF COVID-19 ON THE IT SECTOR: WAS THE ADJUSTMENT AS EASY AS IT SEEMED? THE CASE OF CROATIA - Julia Perić; Ružica Stanić (Economic Review)
The crisis caused by the Covid-19 pandemic affected almost all organizations, regardless of the industry in which they operate. The new working conditions created to protect the health of all employees required a new mindset and a ‘switch’ to more digitalized operations. Many organizations had to adapt or even completely change their business model in order to survive and save jobs. Since digitalized operations were already in place in the IT industry, it seemed that organizations within it had an easier adjustment process to the new pandemic conditions. But have IT companies survived the pandemic as unscathed as it seemed?